Dapatkah Sistem Matrilineal Bertahan Hidup di Kota Metropolitan? - Amri Marzali (Antropologi Indonesia, 2000)
In this article, the author examines whether the matrilineal system is compatible with urban social environment. The case of Minangkabau migrant groups, particularly those from the village of Silungkang, West Sumatra, who now live in the metropolitan city of Jakarta,reveals the incompatability of the two. In Minagkabau region, the combination of the traditional matrilineal system and the residence pattern of duo local are backed up by the wet rice economy and the communal land rights system. In the metropolitan city of Jakarta, these factors are absent. As a result, the matrilineal system does not work.